Development and Validation of an Instrument for the Detection of Early Traumatic Experiences (ExpTra-S) in Patients With Psychosis - Paino, Mercedes; Ordóñez-Camblor, Nuria; Fonseca-Pedrero, Eduardo; García-Álvarez, Leticia; Pizarro-Ruiz, Juan Pablo (Frontiers in Psychology, 2020)
The risk of the appearance of psychosis may reflect the existence of an underlying behavioral vulnerability, which may be influenced by environmental factors such as early traumatic experiences. This means that in clinical practice the assessment of and approach to previous traumatic events is important in patients with psychotic disorders. The psychometric assessmen of trauma has advanced considerably in recent years; however, there is no instrument that has been constructed and validated specifically for the evaluation of early traumatic experiences in the clinical population with psychosis. The main goal of this study was to present the construction and validation process of the Screening of Early Traumatic Experiences in Patients with Severe Mental Illness (ExpTra-S). The sample consisted of 114 patients who had experienced at least one psychotic episode (M= 35.5 years of age; SD= 9.26) and a comparison group of 153 young adults (M= 20.8 years of age; SD= 1.8). The factor analysis revealed an essentially one-dimensional structure. The ExpTra-S was associated with the positive dimension of the psychosis phenotype but not with the negative or affective dimensions, or subjective experiences. No items displayed differential functioning for sex. The ordinal alpha for the total score was 0.96. The patients with psychosis had a higher score for early traumatic experiences in comparison with the non-clinical group. The results obtained showed that the measuring instrument developed, the ExpTra-S, is a brief, simple, and useful measuring instrument for assessing the presence of early traumatic experiences in patients with severe mental illness.